When you're gay, your're outn; Para Mama! Taksi!; Living room animations - Lazaro, Cheche (The Probe team, 1994)
The first part with a lesbian-women relationship who were terminated from their jobs. The second part shows the logistics of taxi drivers in Metro Manila. The last part is about the production of Filipino animation of Nelson and Mina Caligula.